THE INFLUENCE OF INTERNAL AUDITORS’ COMPETENCE AND PROFESSIONALISM ON FRAUD PREVENTION AT THE INSPECTORATE OF BUNGO REGENCY - Azkia, Muti'a; Yudi, Yudi; Friyani, Rita (Faculty of Economics and Business Universitas Jambi, 2026)
This study aims to analyse the effect of internal auditors’ competence and professionalism on fraud prevention at Inspectorate Bungo Regency. The background of this research is the increasing number of fraud cases in regional financial management, which requires internal auditors to play an active role as the frontline of supervision. Internal auditors are expected to possess adequate competence and a high level of professionalism to detect potential irregularities early and provide appropriate corrective recommendations. This study employed a quantitative approach with an associative method. Primary data were obtained through questionnaires distributed to 37 respondents. The data were analysed using multiple linear regression with the assistance of SPSS 30. The results show that partially, internal auditors’ competence has a positive and significant effect on fraud prevention, and internal auditors’ professionalism also has a positive and significant effect on fraud prevention. Simultaneously, competence and professionalism of internal auditors have a positive and significant effect on fraud prevention. These findings emphasize that enhancing the competence and professionalism of internal auditors is a crucial factor in strengthening the internal control system and preventing fraud in local government institutions.